Discurso, espacio y poder en las religions antiguas - Barroso-Romero, Rafael A.,; Castillo Lozano, José Ángel, (Access archaeology., 2021)
14 papers reflect on how the wielders of power, be they religious, social or political, shape the discourses that justify their power within the framework of a society or a specific group, and how space participates in these discourses. Studies consider evidence from epigraphy, the archaeological record, and literary sources.